"No Facts Equals Unconvincing": Fact and Opinion as Conceptual Tools in High School Students' Written Arguments. (July 2018) - Imbrenda, Jon-Philip
In this study, I present a qualitative analysis of 11 writing portfolios drawn from a yearlong instructional program designed to apprentice students into the practices of argumentative writing typical of early-college coursework in the United States. The students' formal and informal writings were parsed into utterances and coded along two developmental dimensions: reciprocity, or the extent to which each utterance answered to the immediate context in which it was generated; and indexicality, or the extent to which each utterance evidenced modes of reasoning that reflect the conventions of academic argumentation. My analysis found that although students' writing evidenced a high degree of reciprocity, they frequently employed nonacademic modes of reasoning. Focusing on a subset of utterances, I show how their tacit orientations toward the concepts of fact and opinion limited the extent to which their reasoning satisfied the evidentiary expectations of formal academic discourse. This discovery suggests that students' development as writers of academic arguments is closely linked to their formal instruction in argumentative writing as well as to their tacit understandings of concepts fundamental to argumentation. Moreover, these findings highlight important distinctions between formal and informal reasoning and how those distinctions may be implicated in both curriculum and instruction.